Integração curricular em tempos de modernidade líquida : uma análise no contexto do curso de Ciências Biológicas do consórcio setentrional - Cezari, Eduardo José (2014)
This paper analyzes the experience of curricular integration in the undergraduate program in Biological Sciences developed in the context of the Northern Consortium. The motivation to develop it derived from the understanding that the experience of curricular organization deserved to be analyzed since it mobilized ten institutions of higher education and a large number of education professionals around a unique project of professor training. It is, therefore, a singular policy of professor training because it was grounded in the collective, inter-institutional and interdisciplinary work. The configuration of the consortium and curriculum analysis is related to several factors, especially with the understanding that the contemporary world is characterized by the disruption of boundaries between nations, territories, institutions and between fields of knowledge. The unstable cartography of the world and of the knowledge that is observed in our time puts modern science in crisis as well as the foundations of technical rationality. The feeling of uncertainty, instability, flexibility, epistemological discomfort we faceexplains why Bauman (2001) refers to our time as "liquid modernity". As we agree with the view of this author we hold as necessary to carry out the analysis of the issue that is the subject of this study from the metaphor of the water and river keeping liaison with the idea of liquid modernity. In this perspective, we take the concept of policy inspired by the approach of the continuous cycle proposed by Ball (1994, 1998, 2002). In the conceptualization defended the policy does not have a fixed place. It is produced in many contexts, a complex process, from the circulation of texts and speeches that before being presented and coded run several meanders silting many senses and propositions. Within the production of the policy clashes, dams, displacement or sublimation of some demands while others are aggregated and channeled into the flow of policy occur. This also occurs in the production of the curriculum both as practical and as text. Concerning the production of an integrated curriculum, an example of which is analyzed here, the dynamics are similar. However, the results motivate the defense of this thesis which may be announced so: In times of liquid modernity the production of professor education policies that transcend boundaries of institutions, courses, knowledge areas and disciplines constitute significant and innovative educational experiences because it potentializes new curriculum cartographies favoring new learning for both students and mentor professors.